2015
DOI: 10.1016/j.joca.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of valgus knee bracing: a systematic review and meta-analysis

Abstract: To review and synthesize the biomechanical effects of valgus knee bracing for patients with medial knee osteoarthritis (OA). Electronic databases were searched from their inception to May 2014. Two reviewers independently determined study eligibility, rated study quality and extracted data. Where possible, data were combined into meta-analyses and pooled estimates with 95% confidence intervals (CI) for standardized mean differences (SMD) were calculated. Thirty studies were included with 478 subjects tested wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 60 publications
1
70
0
Order By: Relevance
“…This combination, or the brace alone, decreases pain and somewhat shifts the load in the knee from the medial to the lateral side. [83][84][85][86][87][88][89] This change in load or contact stress might delay or prevent the onset of OA. In a randomized study in patients with patellofemoral OA, bracing was associated with pain relief and a decreased volume of bone marrow lesions in the affected compartment.…”
Section: Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination, or the brace alone, decreases pain and somewhat shifts the load in the knee from the medial to the lateral side. [83][84][85][86][87][88][89] This change in load or contact stress might delay or prevent the onset of OA. In a randomized study in patients with patellofemoral OA, bracing was associated with pain relief and a decreased volume of bone marrow lesions in the affected compartment.…”
Section: Reviewsmentioning
confidence: 99%
“…In a randomized study in patients with patellofemoral OA, bracing was associated with pain relief and a decreased volume of bone marrow lesions in the affected compartment. 90 These strategies could be used to prevent future OA, but poor compliance is currently a problem, 88,89 and further development of devices and clinical studies are needed.…”
Section: Reviewsmentioning
confidence: 99%
“…The associations between changes in KFM and KAM contributions to the TJM and cartilage thickness ratio changes in the ACLR limb provide support for load modifying interventions to alter gait mechanics following ACLR. For example, gait retraining, bracing, lateral wedging, and specialized footwear can reduce the KAM and could be explored in the ACLR population. Furthermore, extended rehabilitation or interventions aiming to improve quadriceps function/KFM after ACLR could be investigated in future work.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is complicated to determine the isolated effect of loading since it is impossible to measure in vivo loads. For bracing, it has been shown that improvement in pain is small‐to‐moderate while improvement in gait mechanics was moderate‐to‐high . It has also been demonstrated that the placebo effect can play a role in patient experience .…”
Section: Comparison Between In Vitro and In Vivo Overloading Studiesmentioning
confidence: 99%